HUBUNGAN SIKAP IBU DAN DUKUNGAN SUAMI DENGAN PEMILIHAN KONTRASEPSI TUBEKTOMI DI DESA SIALANG KUBANG WILAYAH KERJA PUSKESMAS PERHENTIAN RAJA TAHUN 2016 - Syukrianti Syahda; Herni Wahyuliawati (Jurnal Doppler, 2017)
Tubectomya second surgery on the fallopian tubes of women who lead the person concerned will not get any more offspring. Based on the results of a national survey in 2010 participants of Family Planning (FP) tubektomi only 2.2%, while the target is to be achieved Population and Family Planning Agency (BKKBN) by the year 2014 as many as 27.5% for FPtubal ligation. The aim of research to determine the relationship of the attitude of the mother and support her husband with the contraceptive tubal ligation. This type of research is quantitative analytic using cross sectional design. The population in this study all mothers who indicated tubal ligation in the village of Sialang Kubangfrom January to May 2016 which amounted to 154 people. The sampling technique is total sampling as many as 154 acceptors. The research was conducted on May 30 to June 15 2016. The measuring instrument used was questionnaire. The analysis used univariate and bivariate, processed using computerized systems and chi-square test. The results of this study indicate that (p-value 0.002 <Î± = 0.05) for the attitude of the mother, as well as the support of her husband obtained results (p-value 0.003 <Î± = 0.05), which means there is a significant relationship between mother's attitude and support husband with the contraceptive tubal ligation in the village of Sialang Kubangwork area health center Perhentian Raja. Therefore health personnel should be able to increase the coverage of contraceptive methods tubectomy, by providing counseling to family planning acceptors inhealth centerPerhentian Raja as a follow-up to overcome problems in family planning